Feature Selection and Classification for Sentiment Analysisof Amazon Product Reviews - Daniel, Smita Suresh; Sahu, Neelam; Thomas, Ani (International Journal of Computer Sciences and Engineering, 2025)
Online reviews provide accessible and plentiful data for relatively easy analysis for a given product.This paper seeks to apply and extend the current work in the field of Natural Language processing and sentiment analysis to retrieve information from Amazon Product reviews classify them using Naïve bayes classifier . This work presents a methodology that shows how text data can provide insight into various features of a product found in the customer reviews and feature selection method